Blue Sclera to Brittle Bones: A Rare Case of Osteogenesis Imperfecta With Dentinogenesis Imperfecta and Nephrocalcinosis - Saad Hayat BDS; Ahmad Roshan Mayan BDS; Malik WZ Khan MBBS; Qazi Jawad Hayat BDS (Journal of Investigative Medicine High Impact Case Reports)
Osteogenesis imperfecta (OI) is a rare genetic disorder characterized by bone fragility. Its association with dentinogenesis imperfecta (DI) is well documented, but the concurrent presentation with nephrocalcinosis is uncommon and poorly understood. We documented the case of an 18-year-old male presenting with a triad of OI, DI, and nephrocalcinosis. The patient exhibited characteristic features including blue sclera, multiple fractures, dental abnormalities, bowing of long bones, a short stature, and biochemical evidence of altered calcium metabolism. Genetic testing revealed mutations in COL1A1, confirming the diagnosis of OI Type I. This case highlights the importance of comprehensive evaluation in OI patients, emphasizing the need for dental and renal assessment. The presence of nephrocalcinosis in OI demands further investigation into the mechanisms of calcium dysregulation in disorders of these kinds.